TEACHING-LEARNING READING NATURALISTICALLY AT THE SECOND YEAR OF SMP MUHAMMADIYAH BLORA 2005/2006 - PUSPITA, FRANSISKA ELY (2007)
This research aims at observing the teaching learning-reading at the second year of SMP Muhammadiyah Blora. The research was conducted in SMP Muhammadiyah Blora in 2006. The writer takes the English teacher and students of second year as the subject of the study and the teaching of reading in SMP Muhammadiyah Blora is the object of study. The data are analyzed by using descriptive qualitative method and the writer applies naturalistic research in doing the research. In this research, the data are taken from the event about teaching learning process of English teacher, informant from the teacher and students in SMP Muhammadiyah Blora, and the document is obtained from teaching material and syllabus to complete this research. There are three methods of collecting data namely, observation, interview and data analysis. During 1 month the writer did the observation in SMP Muhammadiyah Blora to get the data. Based on observation, the writer draws some conclusion; (1) the objective of teaching consists of general and specific objectives, 2) the type of syllabus comprises topic-based syllabus which means that the details of lesson taught to the students are not arranged based on the language skills rather than theme, 3) the type and procedure of teaching-learning activities are based on task based instruction. (4) the roles of the students are the subject not the object and negotiator. The roles of the teacher are as manager, facilitator and counselor, instructor and evaluator. To evaluate the student in teaching-learning of reading the way are; (1) the teacher gives a text to the student, (2) the student understand the text, (3) the teacher gives some question about the text to the students, (4) the teacher corrects the students answer.